New Value: Keeping It Real - Peter Chamberlain (ITB Journal Publisher, LPPM ITB, 2013)
Many parts of the world now swim in a sea of complex products that do not necessarily improve the overall quality of our lives. From cell phones to baby strollers, we have overloaded our designed environment with hyper-functional products that often leave us searching for simpler, straighter forward product offerings. In a product landscape that more often than not equates complexity with sophistication; our ever-increasingly complex modern society has allowed faux conveniences to outweigh the tangible realness of our experiences. The look and feel of products has often become complex and complicated